Climate Change and Sustainable Urban Development in Africa and Asia - Yuen, Belinda; Kumssa, Asfaw; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
This book is about African and Asian cities. Illustrated through selected case cities, the book brings together a rich collection of papers by leading scholars and practitioners in Africa and Asia to offer empirical analysis and up-to-date discussions and assessments of the urban challenges and solutions for their cities. A number of key topics concerning housing, sustainable urban development and climate change in Africa and Asia are explored along with how policy interventions and partnerships deliver specific forms of urban development. Audience: This book is intended for all who are interested in the state of the cities and urban development in Africa and Asia. Africa and Asia present, in many ways, useful lessons in dealing with the burgeoning urban population, and the problems surrounding this influx of people and climate change in the developing world.
Foreword -- Preface -- Introduction -- Climate Change, Housing and Liveable Cities -- Climate Change and Urban Development in Africa -- Urban Development, Housing and Urban Poverty in Asia -- Climate Chang and Its Effects on Urban Human Settlement in Africa -- Planning for Sustainable Growth in Singapore -- Climate Change and Housing in Ghana -- Climate Change and Energy Efficiency in Singapore -- Creating Sustainable Living Environment for Public Housing in Singapore -- Climate Change and Housing Issues in South Africa -- Housing and Climate Change in Uganda -- Housing and Climate Change in Vietnam -- Climate Change and Sustainable Development in Chinese Cities -- Climate Change and Its Effect on Cities of Eastern African Countries -- Climate Change and Liveable Cities in Malaysia -- Climate Change and Its Effect on Liveable Cities in Zimbabwe -- About the Contritors -- Index.
Keywords: Geography; Housing; Regional planning; Architecture; Climatic changes; Sustainable development; Geography; Landscape/Regional and Urban Planning; Climate Change; Sustainable Development; Housing; Cities, Countries, Regions; Urbanism